Phytocontrol of Root Knot nematodes in Vegetable Crops of India - Singh, Sohini; Sharma, Charul (Asian Journal of Biological and Life Sciences)
Meloidogyne spp. is a major pest of plants and causes yield loss all over the world in cultivated as well as wild plants. In India, also the major share of destruction of crops is caused by Meloidogyne. In the past few years, various methods were used to control this devastation-causing parasite, so as to prevent the severe yield loss. Most of the methods used were not only harmful to the environment but also to the human population. The present study relates to an important admixture of certain plants decoctions to manage and control the root knot nematode, i.e., Meloidogyne spp. The decoctions thus prepared from these plant extracts are successful in rendering nematodes and/ or their eggs susceptible to infection by microflora. The study renders an economical concoction that is not only fatal to nematodes but also is harmless to human population and can be used as a substitute for environmentally harmful, synthetic hazardous agrichemicals, widely used by farmers and land owners to combat these phytonemas.